PESO INVISÍVEL DAS TELAS SOBRE A INFÂNCIA EM MOVIMENTO (CIPEEX, 2026)
This study aimed to analyze the relationship between screen time and physical activity among 9- and 10-year-old children attending municipal schools in Aparecida de Goiânia. This observational, cross-sectional, and analytical study involved 150 children assessed using the PAQ-C questionnaire. The results showed significant differences between the sexes: girls had a higher average weekly screen time (62.7 hours; SD = 19.9) compared to boys (39.4 hours; SD = 22.3), while boys spent more hours on physical activity (20.6 hours; SD = 8.0) than girls (15.1 hours; SD = 4.1). Correlation analysis revealed a strong negative association (r = -0.60) between screen time and physical activity, indicating that an increase in one variable is associated with a decrease in the other. It is concluded that there is a need for intervention strategies that encourage physical activity and reduce screen time, especially among females, in order to promote healthier lifestyle habits and contribute to the integral development of children.